Three-dimensional dynamic simulation analysis of magnetic flux leakage distribution in broken strands of wire ropes - WEI Mingjiang; ZHAN Weixia; SHANG Yunkun; LIU Jibing; LIU Yao (Gong-kuang zidonghua)
Current simulation studies on the distribution pattern of magnetic flux leakage (MFL) in broken strands of wire ropes primarily use finite element static magnetic field simulation models. In these models, the wire rope and the damage detection instrument remain relatively stationary. However, during actual field inspections, there is relative motion between the wire rope and the detection instrument, leading to deviations between the simulated and actual MFL signals. To address this issue, this study established a three-dimensional dynamic magnetic field simulation model using Ansoft Maxwell electromagnetic simulation software. The model simulated the MFL of broken wires under relative motion conditions and analyzed the effects of different break widths, numbers of broken wires, and lift-off values on the peak-to-peak axial MFL. The simulation results show that the three-dimensional dynamic magnetic field simulation model can replicate the relative motion between the wire rope and the detection instrument. The simulated MFL include both the MFL caused by broken wires and that caused by wire strands, making it more representative of actual leakage fields. The peak-to-peak axial MFL initially increases and then decreases as the break width increases. Additionally, the peak-to-peak axial MFL exhibit a positive correlation with the number of broken wires and a negative correlation with the lift-off value. The accuracy of the three-dimensional dynamic magnetic field simulation model is further validated by establishing a three-dimensional magnetic dipole model to analyze the peak-to-peak axial MFL.